An application of quality function deployment to improve service quality in a cellular mobile telephone company - Macatangay, Leah Alvino
The thesis sought to design the service quality rendered by a cellular mobile telephone company using Quality Function Deployment, a structured methodology, in order to measure and improve service quality. A customer Satisfaction/Quality of Service Enhancement Survey was conducted among subscribers of three cellular phone companies in order to derive the importance they gave to previously identified customer wants and needs, and to assess their present level of satisfaction with the service they currently receive from their service provider. The respondents of Company A rated "Always have a signal" the most important need, followed by "Accurate billing", "Can reach many places", "Pay for calls made", "Clear and continuous reception", and so on. For Company A's cellular service, a design model called the House of Quality was constructed. The results of the survey served as inputs to the first four columns of the Planning Matrix of the House of Quality. The rest of the columns, as well as the other parts of the House of Quality, such as Priorities, Competitive Benchmarks, and Targets were filled in with computed values as well as decisions made by the development team.